Branchial nitrogen cycle symbionts can remove ammonia in fish gills. Issue 5 (27th April 2016) - van Kessel, Maartje A.H.J.; Mesman, Rob J.; Arshad, Arslan; Metz, Juriaan R.; Spanings, F.A. Tom; van Dalen, Stephanie C.M.; van Niftrik, Laura; Flik, Gert; Wendelaar Bonga, Sjoerd E.; Jetten, Mike S.M.; Klaren, Peter H.M.; Op den Camp, Huub J.M.
Summary: Knowledge of the mechanisms by which fish excrete their metabolic nitrogenous waste and insights into nitrogen cycling in aquaculture systems is of utmost importance to improve the sustainable commercial production of fish. In fish, most nitrogenous waste is excreted via the gills as ammonia, a potentially toxic nitrogenous compound. In this study; activity assays, physiological experiments, molecular analysis and microscopy were used to show that the gills of fish harbor a unique combination of hitherto overlooked nitrogen‐cycle microorganisms that can theoretically detoxify excreted ammonia by converting it into inert dinitrogen gas. By doing so, these microorganisms may benefit from the ammonia supply by the host and prevent the build‐up of this compound to toxic concentrations. This novel relationship between vertebrates and microorganisms may shed new light on nitrogen handling by ammonotelic fish species.